Antifungal effect of kaffir lime leaf extract on selected fungal species of pathologenic otomycosis in in-vitro culture medium - Soffian, Mohd Syafwan Mohd (2017)
Introduction: Kaffir lime (Citrus hystrix D.C) has been used for a long time in agricultural and alternative medicine. Kaffir lime leaf (KLL) had been proved effective against certain fungi that could infect human body. This study aims to demonstrate the antifungal effect of KLL extract on pathogenic otomycosis species, particularly Aspergillus niger and Candida albicans. Methods: This is a laboratory-controlled prospective study conducted in Universiti Sains Malaysia. KLL was extracted via Soxhlet extraction method by using 70% ethanol and aqueous, then evaporated using rotary evaporator to a thicker compound. The concentrated extract then freeze dried to obtain powdered form which was diluted to establish five different concentrations of 50 g/ml, 25 g/ml, 12.5 g/ml, 6.25 g/ml and 3.125 g/ml. Sabouraud Dextrose agar (SDA) lawned with tested fungal isolates were inoculated with the extracts using well-diffusion method. Zone of inhibition was measured followed by minimum inhibitory concentration (MIC). Results: There were zone of inhibition for both aqueous and alcohol KLL extracts on Aspergillus niger and Candida albicans growth. Candida albicans has antifungal activities in concentrations of 50 g/ml, 25 g/ml and 12.5 g/ml for both aqueous and alcohol KLL extracts. However, zone of inhibition for Aspergillus niger was obtained only in 50 g/ml concentration for both aqueous and alcohol KLL extracts. Statistically antifungal activity of Aspergillus niger is better by aqueous KLL extracts as compared to alcohol KLL extract with significance difference p<0.001. In contrast, antifungal activity of Candida albicans is better in alcohol extracts as compared to aqueous extract with significance p<0.001. The MIC of KLL aqueous extract against Candida albicans was 12.02 g/ml, KLL alcohol extract against Candida albicans was 10.23 g/ml, KLL aqueous extract against Aspergillus niger was 47.86 g/ml and KLL alcohol extract against Aspergillus niger was 48.97 g/ml. Conclusion: KLL has significant antifungal effect towards pathogenic fungi species causing otomycosis, particularly Aspergillus niger and Candida albicans. The antifungal effect of both aqueous and alcohol KLL are seen more on Candida albicans as compared to Aspergillus niger.